Pengembangan Media Evaluasi Wordwall Menggunakan Berbantuan Kecerdasan Buatan Dalam Pembelajaran Materi SIG, PJ Dan Pemetaan Kelas X IPS SMA Negeri 4 Gorontalo - Nonci, Moh Andi H; Lihawa, Fitryane; Lahay, Rakhmat Jaya (-, 2025)
Development of Evaluation Media using Artificial Intelligence-Assisted Wordwall in Learning Geographic Information Systems, Remote Sensing and Mapping Materials for Class X IPS SMA Negeri 4 Gorontalo". This study aims to produce Evaluation Media using Artificial Intelligence-Assisted Wordwall in Learning Geographic Information Systems, Remote Sensing and Mapping Materials. This study uses a development research method with the ADDIE model as an approach in compiling learning media. In this study there are 5 (five) stages, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The results of the development research were obtained from the results of the validator's assessment which showed that this learning media was declared suitable for use and very valid